Factors that cause Work Fatigue among Shipyard Workers - Rokhati, Siti; Widajati, Noeroel; Dwiyanti, Endang; Elias, Saliza Mohd; Efendi, Andi Aziz; Ardhani, Adinda Novia (Folia Medica Indonesiana, 2023)
Highlights: 1. The focus of this study was on the underlying factors of fatigue among shipyard workers, an area that necessitates further research to attain ideal standards in occupational health and safety. 2. This study can provide companies with material to use when counseling workers on the importance of a healthy nutritional intake in preventing fatigue. Abstract Work fatigue remains a prevalent issue among workers in shipyards, leading to detrimental effects on physical well-being, including a decline in body resistance and productivity. The objective of this study was to analyze the relationship between age, nutritional status, working period, physical workload, noise, and lighting with fatigue levels among hull construction workers. This observational study used a cross-sectional approach with a total population of 112 individuals working in the production line of the Warship Division of a shipbuilding company. The sample size in this study was determined using stratified random sampling, resulting in an assembly of 53 samples. Proportionate stratified random sampling was then employed to determine the sample size for each subgroup of the population. The research data were analyzed using the Spearman correlation test (p<0.005). This study found a significant relationship between work fatigue and nutritional status (p=0.000), with a moderately positive relationship (r=0.511). Additionally, there was a significant relationship between work fatigue and physical workload (p=0.000), with a moderately positive relationship (r=0.531). Noise and work fatigue showed a significant relationship (p=0.010), with a weak positive relationship (r=0.353). Lighting and work fatigue showed a significant relationship as well (p=0.000), but with a moderately negative relationship (r=-0.524). On the other hand, work fatigue did not exhibit any significant relationship with age (p=0.129) or working period (p=0.651). This study establishes a relationship between work fatigue and numerous factors, including nutritional status, physical workload, noise, and lighting. However, age and working period are not related to work fatigue. Thus, it is recommended that companies align job requirements with employees' work capacity and conduct regular assessments of noise and lighting conditions to mitigate work-related fatigue.